Nurses’ Knowledge, Attitudes, and Implementation of Evidence- based Practice in Medina, Saudi Arabia - ALAMRI, AYMAN ATEQ; ALAHMADI, ASHWAQ; ALJOHANI, FATIMAH RASHEED; IBRAHIM, TAGHREED ABDULAZIZ; ALSEHIMI , OHOOD MURSHED; ALHARBI, NEHAL MEJZE; MOHAMMAD, HAWA HASSAN; M ALBALAWI, ABDULMAJEED (Journal of Ecohumanism, 2024)
Background: The EBP is an essential competency that all healthcare professionals, including nursing staff, should master. The importance of EBP lies in that it facilitates the delivery of effective, efficient, and safe patient care. Thus, examining the use of EBP among nurses in Madinah's hospitals is essential. Aim: The aim of the study is to identify the knowledge, attitudes, and practices of nurses regarding evidence-based practice, and the relationship between the subscales. Methods: The study used a descriptive cross-sectional design with a self-administered survey. Results: In this study, the nurses had positive views regarding EBP. Specifically, the knowledge/skills subscale had the highest score followed by the practice subscale and then the attitude subscale. There was a significant difference between nurses' work experiences and knowledge/and skills. There was a significant positive relationship between EBP subscales. Conclusion: The hospitals in Medina need to improve their infrastructure in order to support evidence- based practice (EBP) and research.